THE DESIRE CALLED UTOPIA: á¹¢ADDÄ€M á¸¤USSAIN SOCIALLY SYMBOLIC ACTS IN Uá¸ªRUÇ¦ MINHÄ€ YÄ€ MALÊ¿ÅªN (Universitas Pamulang, 2017)
Abstract Uá¸«ruÇ§ minha ya Mal'Å«n, a novel written by á¹¢addÄm á¸¤ussain, is regarded as a work contains the resistance response or the critique toward colonization and domination of ideology, and certain cultural production. This research tries to reveal whether this novel is aimed to voice the struggles and the critiques toward the occupiers. This research applies the theory of political unconscious by Fredric Jameson. There are three interpretation horizons in this political unconscious. They are narrow political horizon, broader social horizon, and historical horizon. Based on the result of these horizons, it can be concluded that in the surface level, this novel manifests critique toward the foreigners, while in the deep level, there is latent critique toward Iraq. In short, this novel does not only have a stronger struggle toward politic existent mode (the foreigners), but also a weaker struggle toward politic existent mode (Iraqi). Keywords: the political unconscious, horizon interpretation, Fredric Jameson, á¹¢addÄm á¸¤ussain